Peningkatan Kemampuan Bertanya dan Penguasaan Konsep Bahasa Indonesia Menggunakan Metode Bervariasi Siswa Kelas V SD Negeri 021 Muara Langsat Kecamatan Sentajo Raya - Slamet, Slamet (GERAM, 2018)
Preliminary data in several replications were only 5 out of 24 fifth grade students who reached the level of mastery of the material for Indonesian language lessons. During the lesson, students rarely ask questions or respond to the teacher's explanation. To improve the ability to ask students and master the concept of Indonesian students, through the application of various methods. After learning, the students' learning outcomes obtained in the second cycle there were 7 students who received a special category, 8 students with very good categories, 7 students with good categories and 2 students achieved enough categories, and there were no more students in the less category. This shows that in cycle II only 2 students have not been completed according to the defined KKM which is 70. In the second cycle of the meeting there was 1 student who did not ask, 3 students who only came from asking, 6 students asked approaching right and 14 students were able ask well and correctly. While cycle II students' ability to ask has increased, from 24 students there are 20 students who are able to ask well and correctly, 3 students ask almost right, 1 student who still asks carelessly and there are no more students who do not ask. In the learning process in the second cycle learning takes place better than the first cycle, students already understand and are familiar with the learning step, so that it can be concluded through the use of various methods can improve the ability to ask questions and mastery of students' Indonesian concepts.